Study of food waste of farmers' households in Klaten to support food security - Saputro, Wahyu Adhi; Purnomo, Singgih; Salamah, Umi (Anjoro: International Journal of Agriculture and Business, 2021)
Food waste is a global issue that has been around for a long time but is unconsciously becoming more serious. This is also experienced by Indonesia, which also contributes to donating food waste. Food waste can occur from upstream to downstream from production to consumption. Farmers as actors in food production are also not spared from food waste behavior. This study aims to determine what factors affect food waste for farmer households in Klaten Regency. In addition, it provides ways of handling non-consumable food and strategic recommendations for the government in responding to the phenomenon of food waste to support food security. The method used in this research is descriptive-analytical. The number of samples used was 30 farmers in Klaten Regency. The selection of Klaten as the research location was determined purposively because this location is the largest rice-producing area in Central Java. The data analysis method used in this research is multiple regression. The results showed that two variables affect food waste: the level of education and the number of family members. The significance value of the two variables is 0.0000, so that the value is less than the alpha value of 0.05. Inadvertently, some households have processed the leftover food, such as making it as organic fertilizer. In addition, several households provide leftover food to livestock. The strategic step that the government must take in tackling this food waste problem is to conduct a massive campaign and, if necessary, implement it in the education system so that people are more aware of food waste.